Studies of Relation Between Turbidity and Refractive Indeks of Bottled Water in The Area of Banda Aceh by Using Interferometer Murty Method - Nurlaili .; Nasrullah Idris; Adi Rahwanto (Journal of Aceh Physics Society, 2012)
Bottled water is clean water ready to drink quickly without cooking however, it is not all of the bottled water have a good quality. The quality of water can be observed from the optical properties of water, such as clarity and refractive index. A study has been carried out by using interferometer Murty method to know the relation between turbidity and refractive index of the bottled water. The refractive index measurement was carried out for 20 samples from 10 brands of the bottled water. The result of refractive index measurement shows that the refractive index of the water is about 1,1, in averge on the other hand the refractive index of water based on literature is 1,33. Along with the refractive index measurement by using interferometer Murty, turbidity was also measured by using Turbidimeter. The result of measurement show that there is a relation between turbidity and refractive index. The deviation of refractive index values obtained in this measurement from the literature data is because there are some error in the measurement process. By improving the error, better measurement will allow the interferometer Murty to be used to inspect water clarity.